Efficiency of project management in higher education establishments on the example of Gdynia Maritime University = Efektywność zarządzania projektami w jednostkach szkolnictwa wyższego na przykładzie Uniwersytetu Morskiego w Gdyni - Kizielewicz, Joanna; Winiarska, Magdalena; Skrzeszewska, Katarzyna; Szelągowska-Rudzka, Katarzyna (Zielona Góra: Faculty of Economics and Management Press)
Project management is sufficiently described in the source literature. However, numerous published scientific works refer mainly to examples of good practice in project management in business entities, and unfortunately higher education establishments (HEE) are marginally analysed.
Keywords: higher education; project management; performance evaluation; szkolnictwo wyższe; zarządzanie projektami; oceny efektywności